The Design of Building The Creative Characters on Literation Based on Youth Locality: A Case Study in Panti Village, Jember Regency - Asrumi Asrumi; Agus Sariono; Budi Suyanto; Didik S (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
This research aimed to describe the relationship between women and nature in maintaining and preserving the natural environment. The relationship was illustrated in problems 1) the existence of patriarchal power on women of Lou Dempar, which causing sexual violence in the